2018
DOI: 10.1080/2162402x.2015.1078062
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ Th1 to the rescue in HER-2+ breast cancer

Abstract: HER2 overexpression leads to downregulation of MHC class-I. CD4 C Th1 cytokines, IFNg and TNFa, and monoclonal antibodies, trastuzumab and pertuzumab, restore MHC class-I expression, and enable CD8 C recognition and cytolysis. Restoration of the anti-HER2 CD4 C Th1 immune response in combination with HER2 targeted therapy appear to be critical to successful anti-HER2 CD8 C immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, due to the proliferation and metastasis of breast cancer cells (BCCs) remaining after chemotherapy, BC patients still face a relatively high recurrence rate and metastasis rate after being treated, which is the main death cause of them. 2,3 Therefore, it is still a great clinical challenge to deal with the recurrence and metastasis of BC, and it is of great clinical significance to find alternative therapies to replace traditional chemotherapy methods in solving the recurrence and metastasis caused by chemotherapy resistance. 4 A previous study reported that the disorder of histone lysine methylation intensified the invasiveness of BCCs.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the proliferation and metastasis of breast cancer cells (BCCs) remaining after chemotherapy, BC patients still face a relatively high recurrence rate and metastasis rate after being treated, which is the main death cause of them. 2,3 Therefore, it is still a great clinical challenge to deal with the recurrence and metastasis of BC, and it is of great clinical significance to find alternative therapies to replace traditional chemotherapy methods in solving the recurrence and metastasis caused by chemotherapy resistance. 4 A previous study reported that the disorder of histone lysine methylation intensified the invasiveness of BCCs.…”
Section: Introductionmentioning
confidence: 99%